Transglutaminase-Mediated Cross-Linking of GerQ in the Coats of Bacillus subtilis Spores - Ragkousi, Katerina (American Society for Microbiology, 2004)
The spores of Bacillus subtilis show remarkable resistance to many environmental stresses, due in part to the presence of an outer proteinaceous structure known as the spore coat. GerQ is a spore coat protein essential for the presence of CwlJ, an enzyme involved in the hydrolysis of the cortex during spore germination, in the spore coat. Here we show that GerQ is cross-linked into higher-molecular-mass forms due in large part to a transglutaminase. GerQ is the only substrate for this transglutaminase identified to date. In addition, we show that cross-linking of GerQ into high-molecular-mass forms occurs only very late in sporulation, after mother cell lysis. These findings, as well as studies of GerQ cross-linking in mutant strains where spore coat assembly is perturbed, lead us to suggest that coat proteins must assemble first and that their cross-linking follows as a final step in the spore coat formation pathway.